"Bangin" at the Crossroads': A Study of Rural Gangs. (February 2023) - Brown, Timothy C.; Baldwin, Julie Marie; Buchanan, Molly; Krohn, Marvin D.
Previous research on rural gangs in America has found these groups not only to be relatively transitory in nature but also forming during periods of economic recovery. This qualitative study focuses on a community within the impoverished rural Mississippi Delta with an extended history of institutionalized Black gangs with ties to national gang nations. Through in-depth interviews with incarcerated members of the community, many of whom have/had gang ties, we seek to understand the unique conditions that fostered these non-traditional rural gangs. More specifically, we critically examine the relationship between social and structural factors that affected the origins, processes, and persistence of gangs in the area. Our findings highlight the social dislocations influenced by state-abandoned responsibilities and the corresponding adaptations by gangs and their members.